Technological innovation to enhance security of tenure for mineral claim holders. Issue 1 (2nd January 2020) - Ingelson, Allan
Abstract : Since the 1800s, ground staking of mining claims on public lands in the United States and Canadian free entry (FE) systems has successfully facilitated mineral discoveries and mine development. One weakness of ground staking regimes is claim staking disputes that create uncertainty for mineral developers and undermine security of tenure. During the last 19 years, electronic claim map selection systems have been implemented in Quebec, British Columbia, Ontario and other provinces to eliminate both the unnecessary expense of staking claims on the ground and the costs arising from claim staking disputes. Competition, a crucial element of FE, is preserved in the more efficient online claim map selection process. Electronic systems with digital maps created for online claim selection can assist governments in preventing mineral takings claims and compensation payments and avoid some disputes between indigenous peoples and mineral developers experienced in ground staking regimes.